Subjects of Experience: Post-cognitive Subjectivity in the Work of bp Nichol and Daphne Marlatt - Nichols, Miriam (Studies in Canadian Literature, 2000)
Both bp Nichol and Daphne Marlatt have recently been reproached for "an imperialist narrative of nation" and for "feminist essentialism" respectively. The critiques have been aimed at the "subject who knows," when in fact both writers "assume the position of the subject who undergoes," rendering much of the negative criticism irrelevant, because misdirected. Theorists such as Foucault, Derrida, and Kristeva have argued that consciousness is a derivative sociolinguistic product and that the critic should search out blind spots where ideology is received as common sense. Given the notion of the subject-in-process, or the subject undergoing, these theoretical proscriptions are problematic. The work of Nichol and Marlatt contains a double tension between cultural givens and productive becoming. The polemical and politicized disparagement ignores the aesthetic play and intensely subjective aspects of both poets' work.